Hypotension under antihypertensive treatment and incident hospitalizations of nursing home residents - TUFAN ÇİNÇİN, ASLI (My University, 2022)
Background and Objective Hypertension is the most prevalent chronic disease in older adults. Antihypertensive drug use increases with aging. In some studies, hypotension developing under antihypertensive medication use has been indicated as a potential risk factor for morbidity and mortality in older adults. Our objective was to assess the relationship between hypotension under antihypertensive treatment and incident hospitalization of nursing home residents. Methods We detailed blood pressure measurements of the previous 1-year period that were noted regularly at 2-week intervals and studied their mean values. The systolic blood pressure (SBP) and diastolic blood pressure (DBP) thresholds to define low SBP (<= 110 mm Hg) and DBP (<= 65 mm Hg) were derived from our previous study. We noted demographics, number of co-morbidities and regular medications, mobility status, and nutritional assessment via the Mini Nutritional Assessment Short Form. Results We included 253 participants (66% male, mean age 75.7 +/- 8.7 years). The prevalence of low SBP (<= 110 mmHg) and low DBP (<= 65 mmHg) was 34.8% and 15.8%, respectively. Among residents, 4% were bedridden, 15.8% wheelchair bound, 14.5% needing assistance for reduced mobility, and 62.7% were ambulatory. At a median of 15 months of follow-up, hospitalization incidence from any cause was 50.8% (n = 134). Incident hospitalization was more common in the group that had low DBP (odds ratio = 3.06; 95% confidence interval 1.02-9.15; p = 0.04) after adjusting for age, number of comorbidities and medications, mobility status, and nutritional status. Low SBP was not associated with hospitalization. Conclusions The low DBP (<= 65 mm Hg) during the previous year was associated with incident hospitalization of nursing home residents after adjustment for several factors. These findings indicate that lower DBP may be a causative factor for incident hospitalization. We need further studies to explore whether a correction of diastolic hypotension may decrease the hospitalization risk in this vulnerable population.
Keywords: Tıp; Temel Eczacılık Bilimleri; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Health Sciences; Internal Medicine Sciences; Internal Diseases; Geriatrics; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; GERİATRİ ve GERONTOLOJİ; Klinik Tıp; Klinik Tıp (MED); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); GERIATRICS & GERONTOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); Geriatri ve Gerontoloji; İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Geriatrics and Gerontology; Pharmacy; Drug Guides